Makna Kenaikan Kristus dalam Dialektika Teologi Yahudi dan Kristen: Konflik, Tipologi, dan Konsiliasi - Heny Heny (KAPATA: Jurnal Teologi dan Pendidikan Kristen, 2024)
The event of the Ascension of Christ is frequently marginalized within systematic theological discourse, often reduced to a mere chronological epilog to the Resurrection. This article aims to reconstruct the meaning of the Ascension as a Christological climax that bridges the tension between the resurrection narrative and the event of Pentecost. Employing a qualitative method with a canonical and biblical theological approach, this study juxtaposes the Hebrew concept of Aliyah (ascent/migration) and the Merkavah tradition (Chariot of Glory) with patristic doctrines such as Exaltatio (exaltation) and Recapitulatio (recapitulation). The novelty of this research lies in the proposition that the Ascension serves as the momentum for the "naturalization" of humanity into the divine reality. Comparative analysis reveals an ontological conflict: on one hand, rabbinic tradition rejects this claim as a form of shituf (associationism), while on the other, the Church Fathers celebrate it as the foundation of theosis (divinization). Through a philological study of anastasis (resurrection) versus analepsis (assumption), as well as the Hebrew equivalent laqach (taken), this research concludes that the Ascension of Jesus is substantially distinct from the "translations" of Enoch or Elijah, as it involves the personification of humanity within the exclusive throne of the Shekhinah.